Elevated central blood pressure, NT-proBNP and hs-cTnI in women with maternal complications of hypertensive disorders of pregnancy - Xolani B. Mbongozi; Stuart D.R. Galloway; Angus Hunter; Mirabel Nanjoh; Charles B. Businge (Hypertension in Pregnancy, 2025)
Objective The main objective of the study was to compare the levels of CBP and these cardiac biomarkers in women with maternal complications of hypertensive disorders of pregnancy (HDP).Methods This was a cross-sectional study that enrolled 270 women with HDP and 270 normotensive pregnant controls. Data on basic characteristics and incidence of maternal complications were collected among the two groups. Additionally, information on cardiac biomarkers and CBP was gathered from the women with HDP, to compare the levels of these biomarkers with maternal complications experience by this group.Results Non-hypertensive controls were significantly older than hypertensive cases and had a higher median gestational age at recruitment compared to hypertensive cases The median levels of CBP and cardiac biomarkers were significantly higher among hypertensive participants with maternal complications (n = 107/270) than those without complications (n = 163/270). Specifically, central systolic blood pressure (CSBP) was 133 (120–142) mmHg vs 128 (109–129) mmHg (p = 0.033) and central diastolic blood pressure (CDBP) was 75 (62–86) mmHg vs 69 (56–73) mmHg (p < 0.01), while NT-proBNP was 446 (145–1126) vs. 57 (21–167)) pg.ml−1; p < 0.0001, and hs-cTnI was 12 (7–35) ng.L−1 compared to 8 (3–8) ng.L−1; p < 0.0001, in cases v. controls, respectively.Conclusion In conclusion, the study found that pregnant hypertensive women with maternal complications had significantly higher median values of CSBP and CDBP, NT-proBNP, and hs-cTnI in compared to those without complications. These findings suggest that measuring these vital signs and cardiac biomarkers in hypertensive pregnancies might be helpful for screening and monitoring maternal complications.